Antibacterial activity of n-hexane and ethanol extracts of Polycarpa aurata against pathogenic bacteria of shrimp and fish. Issue 1 (1st December 2022) - Lestari, D N; Massinai, A; Haris, A
Abstract: Polycarapa aurata is one of the ascidians from the subphylum Urochordata that produces secondary metabolites that can be used as antibacterial agents. This study aimed to examine the potential of Polycarpa aurata extract as an antibacterial against pathogenic bacteria of aquatic organisms, namely Vibrio parahaemolyticus and Vibrio harveyi . This research was conducted from February to July 2020, including sample collection and preparation, extraction, and antibacterial testing. Samples of Polycarpa aurata were obtained from the reef flat waters of Barranglompo Island, Makassar City. Sample preparation was carried out to produce a dry sample which was then continued in the extraction process by the multilevel maceration method (1:3). The solvents used were n-hexane (nonpolar) and ethanol (polar), which yielded a 1.6% yield of n-hexane extract and 2.21% ethanol extract, respectively. The antibacterial activity test was carried out using the disc diffusion method (Kirby Bauer Test) and measured the average clear zone against the two test bacteria. The n-hexane extract of Polycarpa aurata showed antibacterial potential against Vibrio parahaemolyticus 0.73 mm and Vibrio harveyi 1.24 mm with a weak category. Meanwhile, the ethanol extract of Polycarpa aurata showed weak antibacterial activity against Vibrio parahaemolyticus 4.21 mm and moderate category against Vibrio harveyi 6.69 mm.